Optimal percentage of biventricular pacing to obtain CRT response: how high is high enough. (24th May 2021) - Esteves, AF; Parreira, L; Mesquita, D; Fonseca, M; Farinha, JM; Pinheiro, A; Ferreira, J; Coelho, R; Amador, P; Lopes, A; Fonseca, N; Caria, R
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: The greatest benefit with cardiac resynchronization therapy (CRT) is achieved when biventricular pacing (BivP) percentage (%) is close to 100%. However, in some patients that goal can be challenging to obtain. Purpose: Determine whether a lower BivP% could lead to similar CRT response and events, as compared with patients with BivP% >98%. Methods: Patients with CRT followed up in a remote-monitoring network were retrospectively analyzed. BivP% was assessed and response to CRT was defined as an absolute increase in left ventricle ejection fraction (LVEF) >5% or a relative increase in LVEF >15%. Low BivP% was defined as <98%. Clinical, echocardiographic data and all-cause death during follow-up were evaluated. ROC curve and AUC were obtained to determine the discriminative power of BivP% as predictor of CRT response. Optimal cut-point value was obtained and patients were divided according to this value. Kaplan-Meyer survival function was used to compare survival in the different groups and the Log-rank test was used for comparison between the groups. Results: 88 patients, 76% male, median age 73.5 (IQR 65.75-79.25) years were included. A CRT-D was implanted in 69%. Etiology was ischemic in 44%. 93% were under beta-blockers. Median LVEF before CRT was 27% (IQR 20.25-32). 44 patients (50%) had low BivP% (median 91%, IQR 96-99), 55% due to atrial fibrillation and 52% due to frequent premature ventricular complexes. After optimization of medical therapy, device programming and/or interventional procedures, we obtained a BivP >98% in 26 out of the 44 patients (59%). However, in 18 patients (20%) BivP% was <98% (median 95, IQR 92.25-96). 66% patients were CRT responders. Median follow-up was 36 (IQR 23.75-84) months. During follow-up, all-cause mortality was 27% (24 patients). Optimal cut-point value for predicting CRT response was 91% BivP% (AUC 0.644, p-value 0.047, 95% CI 0.496-0.792). The characteristics of the two groups didn't differ significantly (Table). Survival was significantly higher in patients with BivP% >91% (Log-rank 3.667, p-value 0.050) – Figure. Conclusion: In this population, BivP% >91% was sufficient to achieve CRT-response and was associated with a better survival.